The influence of power driven buyer/seller relationships on supply chain satisfaction - Benton, W.C.; Maloni, Michael (Journal of Operations Management, 2005)
AbstractResearch on supplier satisfaction in buyer–supplier relationships has been primarily conceptual. One purpose of the research described in this paper is to empirically test the influences of supply chain power on supplier satisfaction. Exploration of the effects of power on factors of supplier satisfaction will provide the key to understanding the power‐satisfaction link in supply chain relationships. This paper shows how the buyer–seller relationship affects supplier satisfaction. In doing so, previous satisfaction and power literature is pulled together to demonstrate that the power‐satisfaction variable must be included in any examination of supply chain partnerships. The three primary objectives of this research are to establish how the different “bases of power” affect the satisfaction of selling firms, investigate how power driven relationships affect supplier satisfaction, and measure the effect of power influences on supplier satisfaction in the automobile industry. Each of these research objectives was achieved. This study establishes the first empirical evidence for the measurement of power‐driven supplier satisfaction. In each of the nine models studied, the power‐affected buyer–supplier relationship was found to have a significant positive effect on both performance and satisfaction. The paths between performance and satisfaction, however, were consistently found to be non‐significant.